(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
It is actual problem to distinguish between real gunshot sound pictures from tactical weapons and from fabricated or manipulated ones. In this work, some possible approaches to digital manipulation detection in gunshot records are described. The study uses methods of temporal and spectral analysis, revealing fine changes in signals, in a comprehensive dataset that consist of the raw data of gunshot sounds. The purpose of the work is to consider some approaches to digital manipulation detection in gunshot records High accuracy in the identification of manipulated sounds is demonstrated, with a low percentage of false positives and a high percentage of true positives. This research lays the groundwork for a comprehensive database of gunshot signals. This database has potential value for further analysis using methods like the Continuous Wavelet Transform.